Differences in Working on the Composition Depending on the Individual Characteristics of the Student - Z. Ziyavutdinova (International Journal on Orange Technologies, 2021)
In this article, when working with students on the same work, it is necessary to focus all of them on one goal, perhaps to go deeper into the artistic image and to fully submit the resulting design of the performance. But everyone has their own way to do it. If a teacher has created this or that interpretation, he cannot apply it to everyone and treat each student individually. To teach the student to build his own path from the very beginning, to help him find the necessary goals and to protect him from unnecessary difficulties so as not to get lost. This is the only way to teach him to work independently and develop the most important personal qualities of the student.